Magnetic microswarm for MRI contrast enhancer. Issue 17 (14th July 2022) - Zhang, Zhanxiang; Wang, Haocheng; Yang, Hua; Song, Wenping; Dai, Lizhou; Yu, Shimin; Liu, Xuejia; Li, Tianlong
Abstract: Highly effective contrast enhancer that processes targeting ability and maneuverability is in great demand in clinics for accurate diagnosis. Here a new strategy using deformable and manipulatable magnetic microswarm as MRI contrast enhancer is developed. Magnetic microswarm aggregated from nanoparticles is inherently deformable and they can be controlled with multiple programmable deform abilities. It is demonstrated that spatiotemporal programming magnetic field enables the magnetic microswarm not only to exhibit both ribbon‐like and round‐like behaviours but also to adaptively navigate multiple terrains. Intestinal model is conducted to explore the effect of magnetic microswarm as MRI enhancer, indicating the obvious enhancement of T2 ‐weighted MRI sequences. This magnetic microswarm holds great promise for highly sensitive and accurate intestinal MRI in the clinic. Abstract : In this article, a reconfigurable and mobile magnetic microswarm as MRI contrast enhancer was investigated experimentally and numerically. By changing motion mode, it could adaptively navigate multiple terrains. Furthermore, we demonstrated this microswarm performed great enhancement of MRI imaging. This microswarm held great promise for highly sensitive and accurate intestinal MRI in the clinic.